Phaseolus vulgaris L. TPv-75 - GLIS of the ITPGRFA (International Institute of Tropical Agriculture, 2019)
Plant Genetic Resource.
Taxonomy: Phaseolus vulgaris L.
Common name(s): Kidney bean
Other names: TPv-75
Conserved by: International Institute of Tropical Agriculture (IITA), Nigeria
Local sample unique identifier: TPv-75
Method of creation: Acquisition
Date: 2011-11-01
Historical: No
Biological status: Traditional cultivar/landrace
MLS status: Included
Keywords: Plant Genetic Resource for Food and Agriculture; FOS: Biological sciences; FOS: Agriculture, forestry, and fisheries